A rare triple concurrence of ureteric calculus and renal cell carcinoma in a horseshoe kidney. (16th March 2023) - Munien, Kale; Winston, Joshua; Davies, Nicholas
Abstract: Horseshoe kidney is a rare anatomical variant with low clinical morbidity. However, the characteristic shape of horseshoe kidney causes significant anomalies within the vascular and collecting systems. This complicates the diagnosis and management of coexisting pathologies within the kidneys. Here, we report a rare case of concurrent diagnoses of ipsilateral ureteric calculus and renal cell carcinoma within a horseshoe kidney and describe the subsequent management rationale based on the current literature.